PENGARUH PEMBERIAN KOMBINASI REBUSAN JAHE MERAH DENGAN ASAM JAWA TERHADAPINTENSITAS DISMENORE - Muhriyani Muhriyani (Jurnal Medika Hutama, 2022)
Purpose :This study was aimed to determine the influence against intensity of dysmenorrhea. Method: The design of this research study was “Quasy Experiment” using the draft “Non-equivalent control group” which is divided into an experimental group and control group. The study was conducted to adolescence on Air Manis village. Total sample was 34 adolescence who fit the inclusion criteria and the using simple purposive sampling technique. Measuring intrumenst is used sheets observation numeric rating scale (NRS). The analysis used univariate and bivariate analysis using Wilcoxon test and Mann Whitney test. Result: The result was showed a decrease in the instensity of dysmenorrhea in the experimental group after given red ginger decoction with tamarind with p value (0,000) < (0,05). Conclusion: Red ginger decoction with tamarind can reduce dysmenorrhea in non-pharmacological which can be a practiced independently.